LINGUISTIC TAGGING OF NATIONAL-CULTURAL UNITS IN THE PARALLEL CORPUS OF THE NOVEL “QIYOMAT” (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article provides theoretical information on the internal mechanism of a parallel corpus, the linguistic and cultural adaptation of translation units, the example of a Turkic tagger, the tagging of linguistic and cultural units, phrase models, and structural differences in translation units from unrelated languages, supported by examples. It also explores how these linguistic and cultural units in the novel Qiyomat are formed through metonymy, metaphor, and personification, highlighting the translator’s uniqueness-specifically, their stylistic individuality-and how the national color is embedded in the translation process from the original language to the target language.